A new approach to follow a single extracellular vesicle—cell interaction using optical tweezers. (January 2016) - Prada, Ilaria; Amin, Ladan; Furlan, Roberto; Legname, Giuseppe; Verderio, Claudia; Cojoc, Dan
Extracellular vesicles (EVs) are spherical membrane structures released by most cells. These highly conserved mediators of intercellular communication carry proteins, lipids, and nucleic acids, and transfer these cellular components between cells by different mechanisms, such as endocytosis, macropinocytosis, or fusion. However, the temporal and spatial dynamics of vesicle—cell interactions still remain largely unexplored. Here we used optical tweezers to drive single EVs produced by microglial cells onto the surface of astrocytes or microglia in primary culture. By visualizing single EV—cell contacts, we observed that microglial vesicles displayed different motilities on the surface of astrocytes compared with microglia. After contact, EVs positioned on astrocytes displayed some minor oscillatory motion around the point of adhesion, while vesicles dragged to microglia displayed quite regular directional movement on the plasma membrane. Both the adhesion and motion of vesicles on glial cells were strongly reduced by cloaking phosphatidylserine (PS) residues, which are externalized on the vesicle membrane and act as determinants for vesicle recognition by target cells. These data identify optical manipulation as a powerful tool to monitor in vitro vesicle—cell dynamics with high temporal and spatial resolution and to determine in a quantitative manner the contribution of surface receptors/extracellular protein ligands to the contact.